Spontaneous release of acetylcholine from autonomic nerves in the bladder - Zagorodnyuk, VP (Blackwell Publishing Ltd, 2009)
BACKGROUND AND PURPOSE: Bladder contractility is regulated by intrinsic myogenic mechanisms interacting with autonomic nerves. In this study, we have investigated the physiological role of spontaneous release of acetylcholine in guinea pig and rat bladders. EXPERIMENTAL APPROACH: Conventional isotonic or pressure transducers were used to record contractile activity of guinea pig and rat bladders. KEY RESULTS: Hyoscine (3 µmol·L(−1)), but not tetrodotoxin (TTX, 1 µmol·L(−1)), reduced basal tension, distension-evoked contractile activity and physostigmine (1 µmol·L(−1))-evoked contractions of the whole guinea pig bladder and muscle strips in vitro. ω-Conotoxin GVIA (0.3 µmol·L(−1)) did not affect physostigmine-induced contractions when given either alone or in combination with ω-agatoxin IVA (0.1 µmol·L(−1)) and SNX 482 (0.3 µmol·L(−1)). After 5 days in organotypic culture, when extrinsic nerves had significantly degenerated, the ability of physostigmine to induce contractions was reduced in the dorso-medial strips, but not in lateral strips (which have around 15 times more intramural neurones). Most muscle strips from adult rats lacked intramural neurones. After 5 days in culture, physostigmine-induced or electrical field stimulation-induced contractions of the rat bladder strips were greatly reduced. In anaesthetized rats, topical application of physostigmine (5–500 nmol) on the bladder produced a TTX-resistant tonic contraction that was abolished by atropine (4.4 µmol·kg(−1) i.v.). CONCLUSIONS AND IMPLICATIONS: The data indicate that there is spontaneous TTX-resistant release of acetylcholine from autonomic cholinergic extrinsic and intrinsic nerves, which significantly affects bladder contractility. This release is resistant to blockade of N, P/Q and R type Ca(2+) channels. British Journal of Pharmacology (2009) 157, 607–619; doi:10.1111/j.1476-5381.2009.00166.x; published online 3 April 2009